2012
DOI: 10.1007/s11356-012-1083-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nano-/ultrafine particle-bound PAHs in ambient air at an international airport

Abstract: Concentrations of 22 polycyclic aromatic hydrocarbons (PAHs) were estimated for individual particle-size distributions at the airport apron of the Taipei International Airport, Taiwan, on 48 days in July, September, October, and December of 2011. In total, 672 integrated air samples were collected using a micro-orifice uniform deposition impactor (MOUDI) and a nano-MOUDI. Particle-bound PAHs (P-PAHs) were analyzed by gas chromatography with mass selective detector (GC/MSD). The five most abundant species of P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Characterization of air pollutants from aircraft traffic and airport activity has been primarily conducted at fixed sites located within 2 km of the airport runways (Carslaw et al, 2006; Hsu et al, 2013; Hu et al, 2009; Lai et al, 2013; Lobo et al, 2012; Masiol and Harrison, 2014, 2015; Westerdahl et al, 2008; Zhu et al, 2011) but mobile monitoring has also been used to confirm the area-wide impact of emissions from airport activities on near-airport neighborhoods within a few kilometers (Choi et al, 2013; Hsu et al, 2014). Recently, a mobile monitoring campaign was conducted in the approach path of LAX where a spatially dense sampling scheme uncovered a much larger area of impact covering 60 km 2 and extending 20 km downwind from the airport, the largest monitoring area effort to date (Hudda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of air pollutants from aircraft traffic and airport activity has been primarily conducted at fixed sites located within 2 km of the airport runways (Carslaw et al, 2006; Hsu et al, 2013; Hu et al, 2009; Lai et al, 2013; Lobo et al, 2012; Masiol and Harrison, 2014, 2015; Westerdahl et al, 2008; Zhu et al, 2011) but mobile monitoring has also been used to confirm the area-wide impact of emissions from airport activities on near-airport neighborhoods within a few kilometers (Choi et al, 2013; Hsu et al, 2014). Recently, a mobile monitoring campaign was conducted in the approach path of LAX where a spatially dense sampling scheme uncovered a much larger area of impact covering 60 km 2 and extending 20 km downwind from the airport, the largest monitoring area effort to date (Hudda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These particles are then disseminated in the atmosphere. UFPs represented 15-18% of the particulate concentration in an airport flight path atmosphere (Taiwan International Airport, Taipei, Taiwan) [9] and this rate varied depending on the engine, the type of fuel and climate conditions [10].…”
mentioning
confidence: 99%
“…Other research in the Los Angeles area has found that UFPs contain much higher PAH content than fine (<2:5-lm) particles and coarse (2:5-10-lm) particles (Li et al 2003). With respect to aircraftbased PAHs, a study of emissions within the plane loading area of a major airport showed that the particle-bound PAHs were composed of ∼ 80% high-molecular-weight compounds with high toxicity (Lai et al 2013). Altogether, there is evidence suggesting that UFPs, especially those of aircraft-origin, carry pathogenic PAHs linked to inflammation (den Hartigh et al 2010;Schober et al 2007) and PTB (Wilhelm et al 2011).…”
Section: Discussionmentioning
confidence: 99%